Evolutionary theodicies – an attempt to overcome some impasses - Eikrem, Asle (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2018)
Mats Wahlberg argues that evolutionary theodicies fail to show how an evolutionary process was necessary in order to reach the goal(s) God is said to have had when creating our world. The authors of this article argue that Wahlberg‘s critique fails if one takes into consideration the distinction between type- and token-values. The question that guides Wahlberg‘s discussion is whether or not unique type-values require an evolution in order to be instantiated or not. He does not, however, discuss whether unique token-values require evolution. This article will address this question, and argue that the theodicies he claims to fail does not do so for the reasons put forward by Wahlberg if interpreted as focusing on token-unique values. The authors will also argue that theodicies other than those evaluated by Wahlberg succeed in identifying type-unique values that can only be brought about through evolution.